Integrating Environmental Approval into Mining Business Licensing: Corporate Accountability and Ecological Risk - Febrian Chandra; Rabiq Qalbi (Adagium: Jurnal Ilmiah Hukum, 2026)
This article examines the integration of environmental approval into mining business licensing following the consolidation of Indonesia's risk-based licensing regime. It employs normative legal research using statutory, conceptual, and critical policy approaches, supported by an inventory and systematic interpretation of primary legal materials and recent scholarship. The study finds that integration can improve procedural certainty, but it also produces four accountability-risk indicators: blurred separation between environmental assessment and license issuance, incomplete public decision trails, asymmetric central-regional supervisory authority, and a weak operational link between environmental violations and the status of business licenses. These risks are particularly significant in mining because ecological impacts are spatial, cumulative, and long term. The article proposes a five-stage ecological accountability framework covering pre-licensing, license issuance, supervision, sanctions, and restoration. The framework requires meaningful public participation, accessible environmental data, field verification, responsibility of permit holders and beneficial controllers, and enforceable reclamation and post-mining guarantees. The central argument is that procedural simplification is legally acceptable only when it does not become substantive deregulation of environmental control.